2023
DOI: 10.3390/buildings13010177
|View full text |Cite
|
Sign up to set email alerts
|

Properties Evaluation of Composite Materials Based on Gypsum Plaster and Posidonia Oceanica Fibers

Abstract: Estimating the amount of material without significant losses at the end of hybrid casting is a problem addressed in this study. To minimize manufacturing costs and improve the accuracy of results, a correction factor (CF) was used in the formula to estimate the volume percent of the material in order to reduce material losses during the sample manufacturing stage, allowing for greater confidence between the approved blending plan and the results obtained. In this context, three material mixing schemes of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Plaster gypsum, a semi-hydrated calcium sulfate obtained through dehydration of the gypsum mineral (CaSO 4 .2H 2 O), plays a vital role in the construction industry. Employed in various products such as ceiling tiles, partition blocks, and drywall, gypsum is integral to numerous construction applications (Guedri et al, 2023). However, construction, renovation, and demolition activities result in significant amounts of waste, known as construction and demolition waste (CDW), which includes, in addition to plaster, materials such as wood, concrete, and heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Plaster gypsum, a semi-hydrated calcium sulfate obtained through dehydration of the gypsum mineral (CaSO 4 .2H 2 O), plays a vital role in the construction industry. Employed in various products such as ceiling tiles, partition blocks, and drywall, gypsum is integral to numerous construction applications (Guedri et al, 2023). However, construction, renovation, and demolition activities result in significant amounts of waste, known as construction and demolition waste (CDW), which includes, in addition to plaster, materials such as wood, concrete, and heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of thermal behavior, the lowest thermal conductivity is the criterion for lowering building energy consumption. Studies have suggested insulation materials and demonstrated the benefits of natural waste/fibers such as date palm fibers [14], cellulose fibers [25,26], wood waste [7,27], wheat straw [28], Posidonia oceanica fibers [29], rice straw [18], and Sargassum muticum [30].…”
Section: Introductionmentioning
confidence: 99%
“…Gypsum is a building material with many advantages, such as fire resistance and high sound insulation [20]. According to the 2019 statistical evaluation, the importance of this item can be estimated [21]. For example, production in the United States is estimated at 20 million tons, China at 16 million tons, Iran at 16 million tons, Turkey at 10 million tons, Spain at 7 million tons and Thailand at 9.3 million tons [19].…”
Section: Introductionmentioning
confidence: 99%